Viscosity of a sauce lupine (Lupinus mutabilis ) gluten free and lactose using guar and xanthan gums - Minaya Agueroa, Carmen (2016)
It was formulated and prepared sauce free tarwi gluten, lactose and casein adding xanthan gum in the proportion of 0.7%, packed in glass jars and sterilized at 115° for 30 min, for reporting a higher density equal to 1.1751 g/cm3, value within the density range Huancaina Alacena ranging from 1.1544 g/cm3to 1, 22 g/cm3.It was proceeded to register the viscosities of Huancaina Alacena and tarwi sauce gluten free, lactose and casein, by the RV method, equipment Brookfield model DV-E version 1, the spindle 6 log readings at speeds from 1.5 to 100 rpm with a torque percentage from 10.2% to 74.5%, which are representative readings viscosities, showing very similar viscosities of Huancaina Alacena and tarwi sauce gluten free, lactose and casein, by the RV method, equipment Brookfield model DV-E version 1, the spindle 6 log readings at speeds from 1.5 to 100 rpm with a torque percentage from 10.2% to 74.5%, which are representative readings viscosities, showing very similar viscosities between 1.5, 2, 2.5 and 3 rpm.With values from 67,850 to 41,750 cP, The 9-point hedonic scale was used to obtain a rating of 7 acceptance "like moderately" and descriptive viscosity test referred to a score of 4 to medium viscosity and flows slowly, which give good insight to the product formulated is an alternative in your diet to sectors considered as special schemes.